417 KRAS mutant uterine carcinomas. (13th November 2020) - Kilowski, K; Dietrich, M; Xiu, J; Baca, J; Ahmad, S; Herzog, T; Korn, M; Holloway, R
Abstract : Background: Inhibitors of KRAS mutations (KRASm) disease have shown efficacy in early clinical studies. Data informing about KRASm targeting in endometrial cancer (EC) are lacking. Methods: ECs (n=8336 with various histologies) were queried for presence of actionable mutations (592 genes) and fusions (Whole Transcriptome Sequencing) using Caris Genomic Profiling database. Comparison was done using Fisher-Exact/ChiSquare (p values) and adjusted for multiple tests by Benjamini-Hochberg (q) and Pairwise nonparametric analysis using Wilcoxon Method. Results: a. KRASm is a frequent genotype in Endometrial Cancer. KRASm were detected in 15.2% of EC cases. Code was most frequently mutated, with G12D (31%) and G12V (27%) being the most common subtypes (figure 1 ). b. Biomarkers of immunotherapy response co-occur with KRASm in EC. MSI-H/dMMR and TMB-H (>10 mt/MB) were seen 36.4% and 42.8% in KRASm and 15.9% and 27.9% in KRASwt, respectively (p>0.05). c. BRCA1/2 mutations were detected with equal frequency among KRASm and KRASwt. BRCA1/2 mutations were seen in 6% of KRASm vs 4.6% in KRASwt (p=0.033). d. KRASm are mutually exclusive of oncogenic fusions. No fusions in FGFR1/3, MET, ALK were detected concurrently with KRASm. Overall, incidence of fusion was extremely low, independent of KRAS status. Conclusions: KRASm EC represents a genomically distinct group of endometrial cancers. Targeted therapy using this biomarker should be explored in clinical trials. Overlap exists with predictors of immunotherapy response, suggesting a possible immunotherapy combination option. Clinical trials to evaluate these strategies are needed.